HPA-Axis Hyperactivity and Mortality in Psychotic Depressive Disorder: Preliminary Findings - Coryell, William (2008)
BACKGROUND: The excess mortality associated with depressive disorders has been most often attributed to risks for suicide but diverse findings indicate that depressive disorders also increase risks for cardiovascular (CV) mortality. Among the possible mediators is the HPA-axis hyperactivity that characterizes many cases of relatively severe depressive disorder and severity is characteristic of psychotic depressive disorder. METHODS: The following describes a 17-year mortality follow-up of 54 patients with Research Diagnostic Criteria (RDC) psychotic major depression or schizoaffective, mainly affective, depression. All had baseline assessments that included a 1mg dexamethasone suppression test with post-dexamethasone samples at 8 a.m., 4 p.m. and 11 p.m. RESULTS: Regression analyses showed that both greater age and higher maximum post-dexamethasone cortisol concentrations predicted deaths due to cardiovascular (CV) causes (t = 4.01, p < .001 and t = 3.03, p = .004, respectively); the 11 p.m. cortisol concentration predicted death due to suicide (t = 2.05, p = 0.048). The 4 who died from CV disease had a mean (SD) post-dexamethasone cortisol concentration of 18.0 (6.0) μg/dl while the mean (SD) value for the remaining 50 patients was 7.6 (6.6) μg/dl (t = 3.03, df = 53, p = 0.004). Regression analyses showed the 11 p.m. post-dexamethasone value to be predictive of suicide (t = 2.05, p = 0.048). CONCLUSIONS: Conclusions should be tentative because an earlier follow-up of a more heterogeneous, but larger, sample did not find a relationship between DST results and CV mortality, and because only 4 CV deaths occurred in the present study. HPA-axis hyperactivity is probably only one of a number of factors that link depressive disorder to CV mortality.